ANALISIS JENIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Dewi, Ratna; Putri, Intan Chania; Amrillah, Mu Tasim Bi; Setiawati, Meti; Layisa , Citra (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study analyzes the types of learning diffcultes experienced by students in learning Natural and social scieces (IPAS) in elementary schools. The research method used is qualitative with a case study approach at SDN Ciwedus 1. The results of the study indicate that students' learning difficulties are divided into three main categories: (1) cognitive learning difficulties, experienced by 50% of students and characterized by difficulty understanding the concept of IPAS, (2) difficulties in adjusting social behavior, which include difficulties in social interaction and emotional management, and (3) writing difficulties, which include obstacles in writing neatly and understanding writing rules. This study provides insight for educators in designing more effective learning strategies to overcome students' learning obstacles